Break – Even Analysis as a Management tool for Decision - making in economic institutions Case study an institution: "Premix -Est SPA" SKIKDA (Journal of Economic Additions, 2020)
This paper is designed to explain, by means of concrete examples, the way in which operation conditions changes influence the earnings estimated, as well as the implications of these changes on the decisions to make of Economic institutions.We adopted it in our study On the descriptive analytical method We also adopted in the applied side On Case study an institution: "Premix -Est SPA" SKIKDA .The study revealed that the application of Break – Even Analysis techniques in decision making process to Avery large extent enhance managerial efficiency of Economic institutions, In addition it was revealed that the benefits derived from the application of Cost- volume- profit analysis include: efficient cost control, high productive capacity and increase in profitability.Keywords: Break – Even Analysis; Fixed Costs; Variable Costs; Operating Leverage; Decision making.Jel Classification Codes: M41, L11.